COMBINED ATRIAL SEPTAL DEFECT CLOSURE AND PERCUTANEOUS PULMONARY VALVULOPLASTY FOR SECUNDUM ATRIAL SEPTAL DEFECT AND ASSOCIATED PULMONARY VALVULAR STENOSIS: Combined Atrial Septal Defect Closure - Shabbir, Maj Muhammad; Ahmed, Waqar (Pakistan Armed Forces Medical Journal, 2010)
Congenital pulmonary valve stenosis (PVS) and secundum Atrial septal defect (ASD) are relatively common forms of congenital heart diseases but combination of these two conditions is rare. First successful transcatheter balloon valvuloplasty for Pulmonary valve stenosis was done in 19821. Since then, it has become the treatment of choice for PVS in children with significant transvalvular pressure gradient as well as in adults2-4. Similarly closure of ASD has become the treatment of choice in selected patients5. We report a case of successful concurrent transcatheter balloon dilatation of significant PVS and ASD occlusion in a 5 yrs old male child during the same procedure